2000
DOI: 10.1073/pnas.040575197
|View full text |Cite
|
Sign up to set email alerts
|

Postexposure vaccination massively increases the prevalence of γ-herpesvirus-specific CD8+T cells but confers minimal survival advantage on CD4-deficient mice

Abstract: Mice that lack CD4 ؉ T cells remain clinically normal for more than 60 days after respiratory challenge with the murine ␥-herpesvirus 68 (␥HV-68), then develop symptoms of a progressive wasting disease. The ␥HV-68-specific CD8 ؉ T cells that persist in these I-A b؊/؊ mice are unable to prevent continued, but relatively low level, virus replication. Postexposure challenge with recombinant vaccinia viruses expressing ␥HV-68 lytic cycle epitopes massively increased the magnitude of the ␥HV-68-specific CD8 ؉ popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 42 publications
(44 reference statements)
2
34
1
Order By: Relevance
“…Similarly, adoptive transfer of T cells educated in chronically infected hosts into naive mice is poorly maintained and fails to undergo homeostatic proliferation (60). Interestingly, some persistent infections, such as murine ␥-HV infection, generate CD8 ϩ T cells that appear to be completely functional throughout viral persistence (22,61,62). These Ag-specific CD8 ϩ T cells frequently persist for prolonged periods at high levels and are maintained by increased division compared with rapidly cleared virus infections such as influenza (23).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, adoptive transfer of T cells educated in chronically infected hosts into naive mice is poorly maintained and fails to undergo homeostatic proliferation (60). Interestingly, some persistent infections, such as murine ␥-HV infection, generate CD8 ϩ T cells that appear to be completely functional throughout viral persistence (22,61,62). These Ag-specific CD8 ϩ T cells frequently persist for prolonged periods at high levels and are maintained by increased division compared with rapidly cleared virus infections such as influenza (23).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a lack of CD4 ϩ T cells leads to a lethal wasting disease associated with chronic lytic viral replication (16). This does not reflect CTL exhaustion in CD4 ϩ T cell-deficient mice (17); indeed, there is some increase in their virus-specific CD8 ϩ T cell numbers as the antigen load rises (17), and even massively boosting the CD8 response by postexposure, epitope-specific vaccination does not improve survival (18). Clearly CTLs can respond to some ␥HV-68-infected cells but cannot fully control lytic cycle replication.…”
mentioning
confidence: 99%
“…Vaccination against gammaherpesviruses has been a major goal in preventing gammaherpesvirus-associated morbidity and mortality (22,28,29); however, it has not yet proven efficient in preventing chronic disease (4). Recent studies have demonstrated effective protection from wt ␥HV68 latency (35) by vaccination with a v-cyclin-deficient live attenuated virus; this promising strategy has been predicted to result in prevention of chronic disease.…”
mentioning
confidence: 99%